2010
DOI: 10.1016/j.ejvs.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of 18F-FDG Uptake in Aortic Aneurysm Wall are Associated with High Wall Stress

Abstract: These preliminary observations point to a potential link between high wall stress and accelerated metabolism in aortic aneurysm wall and warrant further large population-based studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 15 publications
6
67
1
Order By: Relevance
“…These observations are extended in the present study. It is worth noting that we were able to correlate the hot spots of 18 F-FDG uptake with high peak wall stress that, in some cases, corresponded to the point of rupture of the aneurysm (22).…”
Section: Discussionmentioning
confidence: 93%
“…These observations are extended in the present study. It is worth noting that we were able to correlate the hot spots of 18 F-FDG uptake with high peak wall stress that, in some cases, corresponded to the point of rupture of the aneurysm (22).…”
Section: Discussionmentioning
confidence: 93%
“…Current guidelines for stable patients recommend surgical or endovascular intervention based largely on aortic dimensions [82,83], although it is well known that rupture can occur in small aneurysms as well. It has been shown that abdominal aortic FDG uptake is associated with higher wall stress [84] and correlates with instability, symptoms and with macrophage infiltration [85]. Whether FDG uptake can identify patients who will benefit from earlier intervention than that dictated by size remains the subject of several ongoing studies.…”
Section: The Potential Of Fdg-pet Imaging In Aortic Aneurysm and Aortmentioning
confidence: 99%
“…Growing evidence show that an increase in 18 F-FDG uptake is a latent signal in the aorta with active atherosclerotic inflammation (59,60). Many studies have attempted to use 18 F-FDG to evaluate aortic diseases (61)(62)(63)(64)(65)(66)(67).…”
Section: Metabolism Activitiesmentioning
confidence: 99%